Food and recipes of the Civil War - Erdosh, George, 1935- (New York : PowerKids Press, 1997)
Briefly describes some of the foods eaten in the North and South before and after the Civil War and the impact of the war on what foods were available and how they were prepared. Includes recipes.
The American Civil War -- Life in the South -- Recipe : hoe cake -- Southern cooking -- Recipe : praline sauce -- Life in the North -- The beginning of the Civil War -- Wartime food in the South -- Wartime food in the North -- What did the soldiers eat? -- Recipe : salt pork in cornmeal coat -- The South is in trouble -- Recipe : sweet potato pie -- Food after the war.
Includes index.
3.6
3-6
Keywords: Cookery, American -- History -- Juvenile literature; Cookery, American -- History; American cooking -- History; Cooking; United States -- History -- Civil War, 1861-1865 -- Juvenile literature; United States -- History -- Civil War, 1861-1865.; United States -- History -- 1861-1865, Civil War